Fuzzy versus probabilistic benefit/cost ratio analysis for public work projects - Kahraman, Cengiz (Zielona Góra: Uniwersytet Zielonogórski)
The benefit/cost (B/C) ratio method is utilized in many government and public work projects to determine if the expected benefits provide an acceptable return on the estimated investment and costs. Many authors have studied probabilistic cash ows in recent years. They introduced some analytical methods which determine the probability distribution function of the net present value and internal rate of return of a series of random discrete cash ows.
Keywords: economic justification; risk; fuzzy set theory; B/C ratio